Parapapillary drusen of the retinal pigment epithelium: original article - Jonas, Jost B.; Jonas, Rahul A.; Jonas, Shefali B.; Panda-Jonas, Songhomitra (Acta ophthalmologica, 2023)
Purpose To describe the occurrence, morphology and associations of parapapillary drusen of the retinal pigment epithelium (RPE-drusen). Methods Using light microscopy, we histomorphometrically examined enucleated human eyes. Results The study included 83 eyes (axial length: 25.9 ± 3.2 mm; range: 20.0-35.0 mm). Eyes with parapapillary RPE-drusen (n = 29 (35%) eyes) as compared to those without drusen had a significantly shorter axial length (24.0 ± 1.8 mm vs 27.0 ± 3.3 mm; p < 0.001), higher prevalence (27/29 vs 12/54; p < 0.001) and longer width (213 ± 125 μm vs 96 ± 282 μm; p < 0.0001) of parapapillary alpha zone, and thicker BM in parapapillary beta zone (8.4 ± 2.7 μm vs 3.9 ± 2.0 μm; p < 0.001) and alpha zone (6.6 ± 3.9 μm vs 4.4 ± 1.5 μm; p = 0.02). Prevalence of parapapillary RPE-drusen was 27 (69%) out of 39 eyes with alpha zone. Beneath the RPE-drusen and in total alpha zone, choriocapillaris was open, while it was closed in the central part of parapapillary beta zone. BM thickness was thicker (p = 0.001) in alpha zone than beta zone, where it was thicker (p < 0.001) than in the region outside of alpha/beta zone. BM thickness outside of alpha/beta zone was not correlated with prevalence of parapapillary RPE-drusen (p = 0.47) or axial length (p = 0.31). RPE cell density was higher in alpha zone than in the region adjacent to alpha zone (22.7 ± 7.3 cells/240 μm vs 18.3 ± 4.1 cells/240 μm; p < 0.001). In the parapapillary RPE-drusen, RPE cells were connected with a PAS-positive basal membrane. Conclusions Parapapillary RPE-drusen as fibrous pseudo-metaplasia of the RPE were associated with shorter axial length, higher prevalence and larger size of alpha zone, and thicker BM in alpha zone and beta zone. The RPE-drusen may be helpful to differentiate glaucomatous parapapillary beta zone from myopic beta zone.
Gesehen am 06.02.2024